Memory for the future: Implications of implicit cognitions in depression. - Liv-Erna Kosnes (2010)
A consistent feature of clinical depression emphasised in several theories is a pessimistic view of one's personal future. The literature divides future cognitions into positive versus negative with reduced positive future cognitions linked to depression and suicidal ideation. This reduction in future cognitions has been linked to impaired autobiographical memory and emotional avoidance. Specifically, a lack of willingness to access personal past experiences influences future cognitions and subsequently future behaviour. Attempted avoidance of painful past events can generalise to reduced contact with all past experiences, positive and negative. The current thesis had three main aims. First, it aimed to determine the differences, or as the emerging literature suggests, the similarities, in thinking about the future and the past in sub clinically depressed versus non-depressed individuals. Implicit future cognitions and past experiences were related to emotional avoidance in a sub clinical sample. The second aim of the current work was to offer an alternative to the use of self report measures in the future and past thinking literature. To that end, a robust and accurate implicit measure of positive future expectations in depression was tested in a sub clinical sample. This implicit methodology proved a better indicator of depression and hopelessness when compared to widely used explicit methodologies. Finally, the thesis aimed to provide analogue evidence of techniques for the remediation of pessimistic thinking as is characteristic in depression, namely mindfulness and values clarification. Mindfulness and values clarification were demonstrated to be useful techniques in the remediation of pessimistic cognitions with increased acceptance of re- or pre-living personally relevant negative experiences allowing for greater psychological flexibility. Taken together the experimental series reported herein suggests that implicit positive cognitions about the past and future are related to sub clinical depression. Additionally, mindfulness- and values-based skills can moderate the link between past and future cognitions and sub clinical depression.